PENERIMAAN APARATUR SIPIL NEGARA (ASN) KABUPATEN BONDOWOSO TERHADAP KONSEP WAKAF PRODUKTIF - Sabila, Shafira Fathia; Manzilati, Asfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Productive Waqf in Bondowoso is still relatively low compared to other surrounding areas. This may be due to the perception of the Bondowoso community that only looks at waqf and the number of people who also do not fully understand the meaning of waqf. One of the major contributors to productive waqf is the State Civil Apparatus (ASN). However, not every ASN who is waqf has a sufficient understanding of waqf. Therefore, the researcher conducted a study of Bondowoso Regency State Civil Apparatus Acceptance (ASN) Against the Productive Waqf Concept with the aim of knowing the effect of the level of understanding, the level of religiosity and information media on the acceptance of the productive waqf concept. This study uses quantitative research methods using primary data obtained by distributing questionnaires to ASN Kab. Bondowoso in the Regional Secretariat. The sample selection used purposive sampling technique with a total of 102 samples. The results obtained are 16 respondents who do not accept the concept of productive waqf and 86 respondents who accept the concept of productive waqf. So the ASN acceptance of the concept of productive waqf is divided into two, some reject and some accept. The level of understanding, the level of religiosity and the information media have an influence on the acceptance of the concept of productive waqf.